2014
DOI: 10.1039/c3ra45029e
|View full text |Cite
|
Sign up to set email alerts
|

A novel one-step synthesis of gold nanoparticles in an alginate gel matrix by solution plasma sputtering

Abstract: We report a novel strategy to produce stable colloidal gold nanoparticles (AuNPs) in alginate aqueous solution which can be done in one step and without any chemicals. The AuNPs were produced by applying a voltage across a pair of gold electrodes which were immersed in alginate aqueous solution.Since the generation of AuNPs was caused by the sputtering of gold electrodes, the process was named the solution plasma sputtering (SPS) process. We utilize the alginate polymer in order to meet three important require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 36 publications
(44 reference statements)
3
61
0
Order By: Relevance
“…1 shows the UV spectra of the CMA and CMA-AuNPs. The LSPR absorption maximum observed at 523 nm confirmed the formation of CMA-AuNPs (Radhakumary & Sreenivasan, 2011).The size of CMA-AuNPs obtained in the present study ranges from 5 to 7 nm and exhibited an absorption maximum at 523 nm and was in good agreement with those reported in literature (Huang & Yang, 2004b;Pal, Esumi, & Pal, 2005;Watthanaphanit, Panomsuwan, & Saito, 2014). To investigate the interaction of different metal ions with CMA-AuNPs, 100 ppm aqueous solutions of metal ions (e.g.…”
Section: Resultssupporting
confidence: 89%
“…1 shows the UV spectra of the CMA and CMA-AuNPs. The LSPR absorption maximum observed at 523 nm confirmed the formation of CMA-AuNPs (Radhakumary & Sreenivasan, 2011).The size of CMA-AuNPs obtained in the present study ranges from 5 to 7 nm and exhibited an absorption maximum at 523 nm and was in good agreement with those reported in literature (Huang & Yang, 2004b;Pal, Esumi, & Pal, 2005;Watthanaphanit, Panomsuwan, & Saito, 2014). To investigate the interaction of different metal ions with CMA-AuNPs, 100 ppm aqueous solutions of metal ions (e.g.…”
Section: Resultssupporting
confidence: 89%
“…These results showed that the nanocarbons grown between electrodes appeared to be formed of stacked layers with a disordered planelike structure and the other nanocarbons formed in the liquid phase were composed of aggregations of small spheres with sizes of 15-30 nm. Comparison of sp 2 and sp 3 carbon components between BZ and BZ_C, or PD and PD_C in XPS C 1s spectra revealed that the ratio of sp 2 carbon components for BZ_C and PD_C was increased, whereas the ratio of sp 3 carbon components was decreased. BET studies demonstrated that the particle sizes of BZ_C and PD_C were much bigger than those of BZ and PD.…”
Section: Resultsmentioning
confidence: 99%
“…This result implies that the type of synthesized nanocarbon differs depending on the position of the reaction field in plasma. The ratio of sp 3 and the C-O component for PD and PD_C increased and became broader than those of BZ and BZ_C, probably affected by the doping of nitrogen atoms to the carbon matrix. A comparison of the N 1s spectra of PD and PD_C in Fig.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarises the zeta potentials for nanoparticles synthesised at different temperatures using chitosan and its grafted copolymers. A large negative or positive zeta potential for suspended particles indicates the system is stable against flocculation or coagulation [56]. In general, the zeta potentials for gold nanoparticles prepared using grafted copolymers show a tendency to be higher compared to those synthesised with chitosan, this could indicate a better stability of nanoparticles synthesised with chitosan grafted copolymers.…”
Section: Synthesis Of Gold Nanoparticles Using Chitosan and Its Graftmentioning
confidence: 93%